Success factors in management indicators for social, solidarity and sustainable social ventures - Guananga Quishpe, Armando; Gamboa-Proaño, Marco; Franco Delgado, Guido; Ibarra Pérez, Luis (REVESCO. Revista de Estudios Cooperativos, 2025)
Social and solidarity economy enterprises constituted predominantly as cooperatives and associations have a growing trend in Ecuador, proving to be an important alternative for a population excluded from the formal labor market. However, these initiatives also show low levels of sustainability, mainly due to weak management capacity affected by scarce knowledge and lack of management tools to promote their permanence and organizational consolidation. The importance of the development of this type of entrepreneurship has forged important research on success factors, leaving a knowledge gap in its practical application. To address this limitation, the present research aims to define management indicators for social and solidarity-based entrepreneurship under a management methodology that allows the integration of success factors. The research is developed through a systemic documentary review and the application of the Delphi method to consolidate the criteria of 20 managers of associations and cooperatives in the process of consolidation of the enterprise. The results show the importance of basing the management of social and solidarity entrepreneurship under a social perspective, where the indicators of collective work, labor integration, institutional relations and environmental protection allow the consolidation of a social capital that promotes a sustainable economic activity.